Antagomir‐155 Attenuates Acute Cardiac Rejection Using Ultrasound Targeted Microbubbles Destruction. Issue 14 (16th June 2020) - Yi, Luyang; Chen, Yihan; Jin, Qiaofeng; Deng, Cheng; Wu, Ya; Li, Huiling; Liu, Tianshu; Li, Yuman; Yang, Yali; Wang, Jing; Lv, Qing; Zhang, Li; et al.
Abstract: Antagomir‐155 is an artificial inhibitor of miRNA‐155, which is expected to be a promising therapeutic target to attenuate acute cardiac rejection (ACR). However, its vulnerability of being degraded by endogenous nuclease and potential off‐target effect make the authors seek for a more suitable way to delivery it. In attribution of efficiency and safety, ultrasound targeted microbubbles destruction (UTMD) turns out to be an appropriate method to deliver gene to target tissues. Here, cationic microbubbles to deliver antagomir‐155 downregulating miRNA‐155 in murine allograft hearts triggered by UTMD are synthesized. The viability of this therapy is verified by fluorescent microscopy. The biodistribution of antagomir‐155 is analyzed by optical imaging system. The results show antagomir‐155 delivered by UTMD which significantly decreases the levels of miR‐155. Also, this therapy downregulates the expression of cytokines and inflammation infiltration. And allograft survival time is significantly prolonged. Therefore, antagomir‐loaded microbubbles trigged by UTMD may provide a novel platform for ACR target treatment. Abstract : Cationic microbubbles composed of DOTAP, DSPC, and DSPE‐PEG2000 are synthesized to carry antagomir‐155 and deliver it to allograft heart in murine by ultrasound targeted microbubbles destruction (UTMD). Sonoporation and cavitation make antagomir‐155 penetrate vascular endothelium into intracellular region of allograft heart. This therapy downregulates microRNA‐155 level in graft heart and attenuates degree of acute cardiac rejection.